(untitled) (Journal of Pharmaceutical Negative Results, 2022)
University educational inclusion has been the subject of several studies at the international level and in the Latin American region in particular. The novelty of the present study lies in the fact that the diagnosis of the object of research has been carried out from a renewed theoretical basis, i.e., the incorporation of theoretical indicators not previously evaluated and which are considered by the authors as key aspects to measure educational inclusion from the viewpoint of university teachers. This made it necessary to design an instrument with technical capacity and scientific rigor, which was subjected to a validation process that provided new research horizons on the subject. A bibliometric review of Educational Inclusion and University Teaching variables was also carried out to know the current status of the scientific production published in high-impact journals indexed in the Scopus database, where the main characteristics within the volume of publications were described.